Just-in-Time Control of Spo0A Synthesis in Bacillus subtilis by Multiple Regulatory Mechanisms - Chastanet, Arnaud (American Society for Microbiology, 2011)

(untitled)
The response regulator Spo0A governs multiple developmental processes in Bacillus subtilis, including most conspicuously sporulation. Spo0A is activated by phosphorylation via a multicomponent phosphorelay. Previous work has shown that the Spo0A protein is not rate limiting for sporulation. Rather, Spo0A is present at high levels in growing cells, rapidly rising to yet higher levels under sporulation-inducing conditions, suggesting that synthesis of the response regulator is subject to a just-in-time control mechanism. Transcription of spo0A is governed by a promoter switching mechanism, involving a vegetative, σ(A)-recognized promoter, P(v), and a sporulation σ(H)-recognized promoter, P(s), that is under phosphorylated Spo0A (Spo0A∼P) control. The spo0A regulatory region also contains four (including one identified in the present work) conserved elements that conform to the consensus binding site for Spo0A∼P binding sites. These are herein designated O(1), O(2), O(3), and O(4) in reverse order of their proximity to the coding sequence. Here we report that O(1) is responsible for repressing P(v) during the transition to stationary phase, that O(2) is responsible for repressing P(s) during growth, that O(3) is responsible for activating P(s) at the start of sporulation, and that O(4) is dispensable for promoter switching. We also report that Spo0A synthesis is subject to a posttranscriptional control mechanism such that translation of mRNAs originating from P(v) is impeded due to RNA secondary structure whereas mRNAs originating from P(s) are fully competent for protein synthesis. We propose that the opposing actions of O(2) and O(3) and the enhanced translatability of mRNAs originating from P(s) create a highly sensitive, self-reinforcing switch that is responsible for producing a burst of Spo0A synthesis at the start of sporulation.